The accuracy of multiple methods for estimating the reaction order of representative thermoplastic polymers waste for energy utilization. (15th January 2022) - Zhang, Wenlong; Zhang, Juan; Ding, Yanming; Zhou, Ru; Mao, Shaohua
Abstract: Thermoplastic polymers are versatile for different fields, and their waste is produced largely. Among the waste treatment methods, pyrolysis is an important method to dispose of thermoplastic polymers waste because of potential energy utilization. Furthermore, accurate pyrolysis kinetic parameters can reflect the pyrolysis process. Therein, reaction order n is an essential factor to characterize reaction kinetics, while the difference between different n values is very small, so the accuracy of n should be paid more attention. To obtain the accurate n value of thermoplastic polymers waste in nitrogen, one representative material called extruded polystyrene (XPS) was studied by using thermogravimetric analysis at five heating rates. The kinetic parameters and thermodynamic parameters were calculated simultaneously, and n was estimated by multiple methods (master plots, model-free, Shuffled Complex Evolution (SCE) and model reconstruction) at heating rates of 10, 30 and 40 K/min. The results showed that XPS waste had important energy potentials, and the n was 2, 2.08, 1.99 and 1.64 for four methods, respectively. Moreover, based on fixed kinetic parameters, the accuracy of n obtained by multiple methods was compared at 3 and 80 K/min not used to estimate kinetic parameters. The accuracy of these methods was: SCE > model reconstruction > model-free > master plots. Highlights: The kinetics and thermodynamic parameters are analyzed simultaneously. The accuracy of reaction order estimated by multiple methods is compared. The Shuffled Complex Evolution (SCE) method has the highest accuracy. Two biomass materials are used to validate the high accuracy of the SCE method.